Penerapan Metode Design Thinking terhadap Pemasaran Produk pada Coffee Shop Rimbun - Raja Ainaya Alfatiha; Iwan Sukoco (Program Studi Manajemen FEBM UMRAH, 2021)
People's enthusiasm for coffee products is increasing, this is also accompanied by an increase in the number of coffee shops. The increase in the number of coffee shops indicates that the competition in the coffee industry will be tougher. So that business people need to determine a strategy to market the product. One method that can be used is design thinking, by going through five stages of empathize, define, ideate, prototype and test. This research is descriptive qualitative by using the type of literature study research. Data collection in writing this article was obtained through primary data, namely interviews and observations and secondary data, namely books, scientific journals, websites, etc. In addition, this article identifies problems using the design thinking method. Based on the results obtained from this article, design thinking can be used as a method of determining marketing and development strategies for Rimbun Coffee Shop